2006
DOI: 10.1016/j.jsp.2006.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Classroom-based cognitive–behavioral intervention to prevent aggression: Efficacy and social validity

Abstract: Classroom teachers need effective, efficient strategies to prevent and/or ameliorate destructive student behaviors and increase socially appropriate ones. During the past two decades, researchers have found that cognitive strategies can decrease student disruption/aggression and strengthen pro-social behavior. Following preliminary pilot work, we conducted a study to determine whether a classwide, social problem-solving curriculum affected measures of knowledge and behavior for 165 4th and 5th grade students a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 27 publications
4
58
0
Order By: Relevance
“…The findings were in line with findings of previous researches [24][25][26][27][28], which indicates the effectiveness of this therapeutic method in decreasing psychological, emotional and behavioral problems like high-risk behaviors. In defining the findings of this research it can be said that in dialectical behavior therapy the basis of change is acquiring skills and proficiencies and creating behavioral incentives, hence Linehan added therapeutic strategies to the treatment that is a reflection of acceptance and validating behavioral capacities and capabilities of current clients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The findings were in line with findings of previous researches [24][25][26][27][28], which indicates the effectiveness of this therapeutic method in decreasing psychological, emotional and behavioral problems like high-risk behaviors. In defining the findings of this research it can be said that in dialectical behavior therapy the basis of change is acquiring skills and proficiencies and creating behavioral incentives, hence Linehan added therapeutic strategies to the treatment that is a reflection of acceptance and validating behavioral capacities and capabilities of current clients.…”
Section: Discussionsupporting
confidence: 91%
“…The results of research show that training cognitive-behavioral strategies decreases aggression, molestation and anger of boys suffering from attention deficit/hyperactivity disorder [24]. Other research findings indicate that employing strategies related to dialectical behavior therapy is effective in decreasing hyperactivity, impulsivity and aggression/riot, and in empowering socially acceptable behaviors, increasing social cognition, and improving relationship with peers [25]. Moreover, other research findings indicate that dialectical behavior therapy is effective in decreasing aggression and controlling rage among teenagers as well as increasing their social competence [26].…”
Section: Introductionmentioning
confidence: 99%
“…Tools for Getting Along (TFGA) is a CBI implemented at the universal level and is designed to prevent or ameliorate emotional and behavioral problems by teaching students to use social problem solving in emotionally-charged situations (Daunic et al, 2006;Smith et al, 2005;Smith et al, 2009). TFGA's most salient characteristic is the structured focus on learning, rehearsing, reviewing, and practicing cumulative steps in a problem-solving sequence.…”
Section: Tools For Getting Alongmentioning
confidence: 99%
“…Findings from two preliminary studies of TFGA showed positive treatment effects on knowledge of problem-solving concepts and variables associated with risk for behavioral difficulties, namely, teacherrated aggression (Daunic et al, 2006), self-reported approach to problem solving, and peer sociometric ratings for girls (see Daunic et al, 2007). These studies were limited, however, by relatively small samples and primarily indirect measures of treatment fidelity.…”
Section: Tools For Getting Alongmentioning
confidence: 99%
See 1 more Smart Citation